2009
DOI: 10.1134/s1070428009090085
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of polyaza macrocycles by palladium-catalyzed amination of 1,2-dibromobenzene and 2-bromo-1,3-dichlorobenzene

Abstract: Palladium-catalyzed amination of 1,2-dibromobenzene with equimolar amounts of linear polyamines leads to the formation of polyaza macrocycles in low yields. The use of 2-bromo-1,3-dichlorobenzene as starting compound ensures considerably larger yields of the target macrocycles, and the reaction is accompanied by side formation of N-aryl-and N,N′-diaryl-substituted polyamines, as well as of cyclic oligomers. The yields strongly depend on the polyamine chain length. Reactions of excess 2-bromo-1,3-dichlorobenzen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…These data show that copper-catalyzed arylation of polyamines is more sensitive to steric factors than palladium-catalyzed reactions because previously we showed that facile amination of o-dibromobenzene and 2,6-dichlorobromobenzene occurred. [39] The N 1 ,N 4 -diarylation of tetraamine 1a with electronrich p-methoxyiodobenzene proceeded normally, and the target product 29 was isolated in 52 % yield (Table 6, entry 5). In this reaction other isomeric diaryl and monoaryl compounds were also obtained as inseparable fractions.…”
Section: Resultsmentioning
confidence: 99%
“…These data show that copper-catalyzed arylation of polyamines is more sensitive to steric factors than palladium-catalyzed reactions because previously we showed that facile amination of o-dibromobenzene and 2,6-dichlorobromobenzene occurred. [39] The N 1 ,N 4 -diarylation of tetraamine 1a with electronrich p-methoxyiodobenzene proceeded normally, and the target product 29 was isolated in 52 % yield (Table 6, entry 5). In this reaction other isomeric diaryl and monoaryl compounds were also obtained as inseparable fractions.…”
Section: Resultsmentioning
confidence: 99%
“…t BuONa as a base. Usually, the Pd-catalyzed diamination of the ortho -dihalogenoarenes is hindered because the introduction of the first amino group decreases the reactivity of the resting halogen atom [ 60 , 61 ]. In our case, the application of 4 equiv.…”
Section: Resultsmentioning
confidence: 99%
“…The much higher reactivity of the primary amino groups than that of the secondary amino groups in the Pd-catalyzed amination reactions is well established and ensures the formation of the corresponding macrocycles [ 62 ]. However, polyamines are better chelators for palladium than oxadiamines and can lead to a decrease in the efficiency of the process and diminish the yield of the target products [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Because of steric and electronic hindrances created by the amino group introduced first, o-dibromobenzene gave rise to macrocycles in lower yields (12-25%) [78]. Using 2,6-dichlorobromobenzene having an additional electron-withdrawing substituent, we succeeded in raising the yield by 10-15% [79] (Scheme 11). The highest yield (56%) of macrocyclic compound was obtained in the reaction with m-dibromobenzene [80] (Scheme 12).…”
Section: Cyclic Oligomersmentioning
confidence: 91%